Antagonistic Activity and Mode of Action of Phenazine-1-Carboxylic Acid, Produced by Marine Bacterium Pseudomonas aeruginosa PA31x, Against Vibrio anguillarum In vitro and in a Zebrafish In vivo Model - Zhang, Linlin; Tian, Xueying; Kuang, Shan; Liu, Ge; Zhang, Chengsheng; Sun, Chaomin (Frontiers in Microbiology, 2017)
Phenazine and its derivatives are very important secondary metabolites produced from Pseudomonas spp. and have exhibited broad-spectrum antifungal and antibacterial activities. However, till date, there are few reports about marine derived Pseudomonas and its production of phenazine metabolites. In this study, we isolated a marine Pseudomonas aeruginosa strain PA31x which produced natural product inhibiting the growth of Vibrio anguillarum C312, one of the most serious bacterial pathogens in marine aquaculture. Combining high-resolution electro-spray-ionization mass spectroscopy and nuclear magnetic resonance spectroscopy analyses, the functional compound against V. anguillarum was demonstrated to be phenazine-1-carboxylic acid (PCA), an important phenazine derivative. Molecular studies indicated that the production of PCA by P. aeruginosa PA31x was determined by gene clusters phz1 and phz2 in its genome. Electron microscopic results showed that treatment of V. anguillarum with PCA developed complete lysis of bacterial cells with fragmented cytoplasm being released to the surrounding environment. Additional evidence indicated that reactive oxygen species generation preceded PCA-induced microbe and cancer cell death. Notably, treatment with PCA gave highly significant protective activities against the development of V. anguillarum C312 on zebrafish. Additionally, the marine derived PCA was further found to effectively inhibit the growth of agricultural pathogens, Acidovorax citrulli NP1 and Phytophthora nicotianae JM1. Taken together, this study reveals that marine Pseudomonas derived PCA carries antagonistic activities against both aquacultural and agricultural pathogens, which broadens the application fields of PCA.